PEMBERANTASAN KEJAHATAN TRANSNASIONAL PENYELUNDUPAN BENDA CAGAR BUDAYA MELALUI HUKUM NASIONAL DAN KERJA SAMA INTERNASIONAL - Aji Lukman Ibrahim; Rianda Dirkareshza (Penerbit Universitas Atma Jaya Yogyakarta, 2020)
This research aims to know law enforcement against transnational criminals smuggling cultural heritage objects through national law and to know the efforts of the Indonesian government to return cultural heritage objects from any other country. This study uses normative legal research, data sources in the form of secondary data consisting of primary legal materials, secondary legal materials and tertiary legal materials. Data analysis is descriptive-analytical with the statutory approach and conceptual approach. The results showed that law enforcement against transnational criminals smuggling objects of cultural heritage both Indonesian and foreign citizens can be enforced using criminal provisions as regulated in Law Number 11 the Year 2010 concerning Cultural Heritage. This is based on the territorial principle and the passive national principle. The efforts of the Indonesian government to return cultural heritage objects from abroad can be done with diplomacy, Interpol cooperation, buy the Cultural Heritage objects from collectors, exhibitions with other countries and borrowing foreign museum collections for long term to complete the museum collections in Indonesia.